2022
DOI: 10.7759/cureus.25347
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Neonatal Outcomes in Pregnant Women With SARS-CoV-2 Infection Complicated by Hepatic Dysfunction

Abstract: Background and objective The coronavirus disease 2019 (COVID-19) pandemic has caused one of the most devastating healthcare crises in recent times and presented many diagnostic challenges and uncertainties. COVID-19 complicated by acute hepatic dysfunction is a well-described phenomenon, but its impact on maternal and perinatal outcomes is not well documented. In this study, we aimed to evaluate the maternal and neonatal outcomes in pregnant women with COVID-19 complicated by liver dysfunction and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…For example, in the case by Arslan et al [ 118 ], the patient’s proteinuria was concerning for pre-eclampsia and liver enzymes trended down as expected after cesarean delivery, though both maternal and neonatal outcomes were poor which complicates interpretation of the case. Similarly, in the case by Choudhary et al [ 111 ], hypoglycemia and elevated bilirubin were highly suspicious for AFLP, but liver enzymes remained elevated for multiple days after delivery.…”
Section: Obstetric Populationmentioning
confidence: 75%
See 4 more Smart Citations
“…For example, in the case by Arslan et al [ 118 ], the patient’s proteinuria was concerning for pre-eclampsia and liver enzymes trended down as expected after cesarean delivery, though both maternal and neonatal outcomes were poor which complicates interpretation of the case. Similarly, in the case by Choudhary et al [ 111 ], hypoglycemia and elevated bilirubin were highly suspicious for AFLP, but liver enzymes remained elevated for multiple days after delivery.…”
Section: Obstetric Populationmentioning
confidence: 75%
“…A retrospective cohort study of 122 COVID-19 positive pregnant patients in Istanbul found acute liver injury conferred a 3.5-fold risk of becoming critically ill during hospitalization[ 112 ]. Maternal mortality is reportedly more common in pregnant patients who delivered while COVID-19 positive with acute liver injury than COVID-19 positive without liver injury[ 111 ].…”
Section: Obstetric Populationmentioning
confidence: 99%
See 3 more Smart Citations